“Adaptación de híbridos tropicales de maíz amarillo de al calidad proteica en el distrito de Juan Guerra-San Martín” - Rojas Chumbe, Percy (2005)
The present investigation work with the objective of evaluating the adaptation of hybrid Tropical of yellow Corn hard of high quality proteica and to determine the relationship beneficio/costo of the hybrid ones introduced in the valley of the First soil May, County of San Martin, geographically characterized to present the coordinates of longitude West with 76º5 '; 6º35 'of South latitude and 356 meters on the level of the sea; the yield was evaluated and characteristic vegetative, using the one designad statistical block completely randomizado (DBCR) with 03 repetitions and 14 treatments, the results were analyzed by means of the variance analysis and the test of multiple significance of Duncan. The results obtained according to the statistical analysis, you concludes that there were significant differences among the treatments in the grain yield to 14% of humidity whose yields fluctuated among 4 699 to 3 954 Kg/ha that correspond the hybrid CMSQ 993004 and CMSQ · 003006. The Marginal one 28 Tropical as local variety and normal corn stood out among the three better hybrid of high quality proteica with 4 620 Kg/ha. according to characteristic agronomic, it was determined the hybrid CMSQ 993004 of grain yellow semidentado and CMSQ 003002 of grain crystalline yellow as promissory of good yield and economically profitable, with net values that overcome the four hundred new suns, for each hectare of production, with a relationship 1 benefit cost of 1, 1 O.